New records of Xerotyphlops vermicularis (Merrem, 1820) indicate the northernmost locality of the species in the Balkan Peninsula - Teodora Koynova (Pensoft Publishers, 2021)
The Xerotyphlops vermicularis (Merrem, 1820) complex represents small, burrowing snakes that occur from the Balkan Peninsula to Afghanistan and generally they are mostly observed during the springtime. In the present study, we report new records of this snake (10 individuals observed) from Elenite village in coastal Bulgaria. According to current knowledge, they represent the northernmost locality of the species in the Balkan Peninsula. We expand the known distribution of X. vermicularis and help to fill information gaps.